(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
Electrical resistivity tomography (ERT) in an aquatic environment is usually measured using two basic systems. One system uses floating electrodes, which is usually applied in shallow water, and the other uses underwater cables with integrated electrodes, which is often carried out as a mobile system. The aim of this research was to test an underwater ERT measurement with floating cables on the water surface, but with electrodes submerged at the water bottom. This type of cable spread makes it possible to lay all the electrodes vertically to the bottom without the distance between them being reduced by the uneven topography and various underwater obstacles. Prior to the field survey that was conducted in a 40 m – deep lake, the response of common electrode arrays was tested using synthetic models. Two models were used that correspond to the geological condition in the field, higher resistivity bodies in a lower resistivity environment and a model with inverse relationship of resistivity to the first one. The Wenner‑Schlumberger and dipole-dipole arrays resolved the resistivity range, size and shape of the bodies very well and were therefore used in the field. The field data quality was very good and it was shown that ERT measurements in freshwater depths of more than 40 metres can provide very good results. As expected from the modelling, the dipole-dipole array led to a high-resolution resistivity model that enabled the characterisation of the lakebed sediments.